Penerapan Behavior Based Safety (BBS) dalam Meningkatkan Kepatuhan Kerja di PT. XYZ - Annisa Putri Prayetno; Dinda Olivia Nur’Aini; Farhad Aidillah Ahmad; Naysilla Mahpuja Putri; Dzaky Almer Syarifullah; Aqsha Nagata Gillardi; Stevent Gusmawo Simanjuntak; Anis Rohmana Malik (JURAL RISET RUMPUN ILMU TEKNIK, 2025)
This study evaluates the implementation of Behavior Based Safety (BBS) in improving occupational safety compliance at PT Wichindo Pratama, a heavy equipment manufacturing company with high work risks. The topic was chosen due to frequent violations of safety procedures, such as the improper use of Personal Protective Equipment (PPE) and neglect of Standard Operating Procedures (SOP), which increase the risk of accidents. A qualitative method was used through direct observation, in-depth interviews with 12 shift workers, and field assessments of safety facilities. The findings show that although the company has an Occupational Health and Safety (OHS) management system, non-compliance still occurs. Issues include incomplete PPE usage, disorganized work tools, and unsafe rest habits. Observations revealed potential hazards such as physical (noise), chemical (oil exposure), ergonomic (awkward postures), mechanical (machine use without full PPE), biological, and psychological risks (stress from shift work). BBS is seen as a strategy to connect existing OHS policies with safe work behavior by focusing on mindset and daily habits. The implementation of BBS is expected to reduce accidents and support the creation of a safer, more sustainable workplace.